Analysis of the Causes of Crooked Sugarcane Crepe Shafts in Sugar Factories: Analisa Penyebab Poros Krepyak Tebu Terjadi Bengkok Di Pabrik Gula - Wasiana, M.Rizky Faisal Dermawan; Iswanto, Iswanto (Procedia of Engineering and Life Science, 2024)
Practical work is a form of education and vocational implementation that is followed by students so that students can work directly in the business world as well as industry or fabrication. Practical work aims to prepare students to become productive human beings and can immediately work in accordance with their respective fields, students can also feel the atmosphere of production and can help deal with some problems- problems experienced by Engineering professionals inside the factory. Therefore, in welding, knowledge must accompany practice, in more detail it can be said that the design of building construction and machines with welded joints, must also be planned about welding methods. This method of inspection, welding material, and type of weld to be used, based on the function of the building parts or machines designed. Based on the definition of DIN (Deutch Industrie Normen) Galvanized Welded Broken Products is the best way to assemble or connect constructions and products made from iron. This welding method is specifically performed for galvanized materials. The iron welding process requires special preparation and skills. Based on the results of fieldwork practices that have been carried out in CV. Sumber Agung Widodo, The process of making panel tables is carried out into several stages, namely the hollow iron cutting, 45- degree galvanized angle cutting, iron plate cutting, elbow iron cutting, splicing by welding, frame painting, and mounting a series of panels to the finished panel table. The materials used are hollow iron, iron plate, elbow iron, iron paint, wheels. The tools used are ac current welding machines, grinders and elbow rulers. Stage Highlights : Practical work enhances students' readiness for the industrial environment. Welding methods must align with building construction and machine design. Fieldwork at CV. ABC involves various stages, including cutting, welding, painting, and assembly. Keywords : Practical work, Welding methods, Galvanized Welded Products, CV. ABC, Iron welding process